Analytical Study of Competency Mapping and Employees Effectiveness of Private Banks in Urban Jhansi: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Technological innovation lays down several changes which can affect the functioning of the human resource and make it simpler and faster than earlier. Human resource management has always played a very important role in improving and enhancing the performance of organization. HR is the most valuable assets of an organization which never depriciate. Build people to build the organization to build business is an accepted truth. The use of Information and Communication Technologies (ICT) facilitates the innovative ways of carrying on HR work. E-Personel management may be most powerful driving force for achieving organizational effectiveness. EHRM has made few buzzword like automation, transparency, empowerment, paperless office with least human interference, a reality which was once supposed the panacea for all the ills of workplace.